Peningkatan Kemampuan Literasi Awal Anak Prasekolah melalui Program Stimulasi - Hapsari, Widyaning; Ruhaena, Lisnawati; Pratisti, Wiwien Dinar (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Stimulation program is a treatment by providing literacy packages containing guidebooks literacy activities, media literacy in children and socialization for mothers. The purpose of this study was to test the effectiveness of the stimulation program to improve literacy skills in preschoolers. The proposed hypothesis that stimulation literacy program effective in improving early literacy skills in preschool children. This research method using a quasi-experimental design with the non-equivalent control group. Subjects were 30 children aged 3-5 years were divided into an experimental group and a control group. Based on the analysis by the non-parametric statistical test Mann-Whitney U, it was known that there were differences increase early literacy skills in the experimental group and control group. Qualitative analysis showed an increase in the literacy skills by observing changes in the measurement results. Results from this study are important as a new study in finding alternative methods of stimulating preschool children.Abstrak : Program stimulasi merupakan perlakuan dengan memberikan paket literasi berisi buku panduan aktivitas dan satu set media literasi pada anak serta sosialisasi untuk ibu. Tujuan penelitian untuk menguji efektivitas program stimulasi dalam meningkatkan kemampuan literasi pada anak prasekolah. Hipotesis yang diajukan yaituprogram stimulasi literasi efektif dalam meningkatkan kemampuan literasi awal pada anak prasekolah. Metode yang digunakan yaitu quasi experiment dengan desain non-equivalent control group. Subjek merupakan 30 anak usia 3-5 tahun yang terbagi menjadi kelompok eksperimen dan kontrol. Berdasarkan hasil analisis dengan uji statistik non-parametrik Mann-Whitney U, diketahui bahwa terdapat perbedaan peningkatan kemampuan literasi awal pada kelompok eksperimen dengan kelompok kontrol. Analisis kualitatif menunjukan peningkatan kemampuan literasi dengan mengamati perubahan hasil pengukuran. Hasil penelitian ini penting sebagai kajian baru dalam menemukan alternatif metode stimulasi anak prasekolah.